(untitled) (Biocenosis, 2015)
The history of the Environmental Education and interpretation in Costa Rica goes back to the 70s, when the development of the international policies in these areas occurred. We present a description of the evolution of these disciplines from its origins until now, from a four-levels approach: (1) the National System of Conservation Areas, (2) the Ministry of Public Education, (3) the public universities and (4) NGOs. For this aim, we present the results gathered from an exhaustive literature compilation and 20 interviews applied to several experts in Environmental Education and Interpretation in the country. The results show a strong institutional development of Environmental Education in the country. However, in the future it seems necessary to address the issue of coordination among institutions, their continuity in time, and the role to be played by environmental interpretation.